Nodul Pita Suara (Singer’s Nodes) - Natalia Yuwono; Stevani Novita (Cermin Dunia Kedokteran, 2014)
Nodul pita suara yang sering disebut dengan “Singer’s Nodes”, “Screamer’s Nodes”, atau “Teacher’s Nodes“ adalah pembengkakan pita suara bilateral dengan ukuran bervariasi yang ditemukan di bagian tengah membran pita suara. Nodul ini memiliki karakteristik berupa penebalan epitel dengan berbagai tingkat reaksi inflamasi pada lapisan superfisial lamina propia. Penyalahgunaan suara (vocal abuse) menjadi penyebab tersering nodul pita suara. Strategi penanganan secara konservatif; terapi wicara merupakan terapi paling utama.Vocal cord nodule also called singer’s nodes, screamer’s nodes or teacher’s nodes is bilateral swelling of the mid-portion of the membranous vocal folds. They are of variable size and are characterised histologically by thickening of the epithelium with a variable degree of inflammation in the underlying superficial lamina propria. Vocal abuse is commonly the etiology of vocal cord nodules. Treatment strategies should be conservative; speech therapy is the primary treatment. The patient is taught to use the voice appropriately, to promote regression of the vocal cord nodules.